Democratic Republic of Timor-Leste : 2008 Article IV Consultation; Staff Report; Staff Statement; Public Information Notice on the Executive Board Discussion; and Statement by the Executive Director for the Democratic Republic of Timor-Leste. - International Monetary Fund. (Washington, D.C. : International Monetary Fund, 2008)
Timor-Leste's initial efforts to develop a stable and healthy economy have been interrupted by the civil unrest of the past two years. The security situation remains fragile and an economic burden. The key challenge remains how to manage the abundant petroleum revenue to alleviate near-term social problems and develop a sustainable non-oil economy. Growth has rebounded in 2007, although the civil unrest continues to undermine the economy. Inflation has risen sharply, but remains low relative to regional comparators. Access to financial services remains limited and credit growth has stalled.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet